Monitoring and Evaluation of Information Sources and Services in the Digital Era: A Study of Law College Libraries and Information Centres in Karnataka (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The digital revolution has redefined the landscape of information creation, dissemination, and utilization across academic institutions. Law college libraries, as key centres for legal learning and research, are at the forefront of this transformation, integrating both print and digital resources to support academic and professional excellence. The increasing reliance on electronic databases, online journals, and digital repositories necessitates effective monitoring and evaluation mechanisms to ensure quality, accessibility, and user satisfaction. This study investigates the monitoring and evaluation practices adopted by law college libraries and information centres in Karnataka State in managing information sources and services within the digital framework. A descriptive survey method was employed, utilizing structured questionnaires and semi-structured interviews with library professionals from various law colleges affiliated to universities across the state. The findings reveal that while a majority of libraries have transitioned toward hybrid or fully digital systems and subscribed to key legal databases such as SCC Online, Manupatra, and HeinOnline, formal mechanisms for assessing their performance and impact remain underdeveloped. The study further identifies major challenges including inadequate ICT infrastructure, limited technical expertise, and insufficient policy support for systematic evaluation. The paper emphasizes the need for strategic interventions such as capacity-building programmes, user feedback integration, and adoption of technology-driven monitoring tools. The research concludes that institutionalizing regular evaluation practices and strengthening digital competencies are essential for enhancing the efficiency, accountability, and user orientation of law college libraries in the digital era.